The Mutual Inductance Effective Permeability and its Application - Csurgai, P.; Kuczmann, M. (Acta Technica Jaurinensis, 2012)
Self inductance effective permeability is used to simplify the magnetic equivalent circuit of an inductor with magnetic core. It represents how the high magnetic permeability material (e.g. ferrite core), which takes place only in some area around the coil winding, influences the electrical characteristics of the inductor. Similarly the mutual inductance effective permeability can be introduced, which represents how the magnetic core of the inductor influences the surrounding external magnetic field and the flux density inside the magnetic core. The mutual inductance effective permeability can be used to calculate the sensitivity of transponder coils or antenna coils in wireless communication or RFID applications. It is also capable of comparing different coil constructions, or can be used for optimization of a design to achieve the desired sensitivity. The calculation should be carried out by numerical methods because of the inhomogeneous medium. Due to the simplicity of the problem the hardware and computation time requirements are relative low, which allows the handling of very complex geometries without simplification. The accuracy of the method was tested on market available Transponder coils, and the computed results were in good agreement with the measured sensitivity.